Headache service management: a new approach to providing more robust and equitable care across the UK. Issue 8 (2nd August 2022) - Gordon, Alexander; Lashley, Daniel; Weatherby, Stuart
Abstract : Headaches are common conditions, but can represent a significant burden to patients, healthcare services and the wider economy. Gordon et al outline how headache services could be made more effective and equally accessible in the UK.